Leadership: a glance from directors, teachers and students viewpoint - Sánchez, Verónica; Tapia, Carmen; Becerra, Sandra (Revista de Psicología, 2006)
Considering scholastic management from a global perspective, it is important to acknowledge that learning efficiency in students and faculty effectiveness are affected by leadership.The purpose of the present research was to learn the meaning that directors, teachers and students attribute to the concept of leadership in three different educational establishments, that is, public, subsidized and private establishments, in Temuco (IX Region, Chile).The sample was constituted by 189 subjects. In order to obtain access to the meaning, Natural Semantic Networks (Valdez, 1998) was used. A total J value of 1407 concepts were obtained indicating the semantic wealth of the network. The total SAM group was constituted by the concepts of leader, responsibility and chief. Regarding the similarities due to roles, responsability and chief appeared as important aspects for leadership. There were differences between the networks of directors and teachers who considered a more participative leadership, vr. the students, who stood out a more authoritarian one.